Glucose Templated Hydrothermal Synthesis of Porous Nanocrystalline Anatase TiO2 - KARTINI, INDRIANA; Evana,; Chotimah, (Asian Journal of Chemistry, 2010)
Synthesis of porous nanocrystalline anatase TiO2 was performed hydrothermally employing glucose as the pore-forming agent. It was found that at low concentration, glucose has played dual actions of pore generating agent and anatase crystalline phase stabilizer. It is supposed that the presence of open chain aldehyde as isomeric structure of glucose acting as the oxygen supplying agent in inducing the anatase crystalline phase. The resultant porous TiO2 powders were composed of highly uniform rounded rectangular shape particles generating surface area as high as 74.9 m2/g with Barrett-Joyner-Halenda (BJH) pore diameter of 12.9 nm, indicative of mesoporosity. Photosensitized TiO2 film by dye extract of mangosteen fruit pericarps has generated reasonable photocurrent with an open circuit voltage of 0.35 V.